Al-Imam Ibn Qayyim (691-751h11292- 1350m): Sorotan Terapi Ruqyah dalam Pemikiran Perubatan - Mohd Yusoff, Mohd Yakub @ Zulkifli; Haron, Zulklflee (Jurnal Usuluddin, 2010)
It is a need to tutclerstancl that the medical method in Lslam has dilJbrent nteaning than any other medical. Islant celebrates fito nta.jor aspects of’human events namely body ond soul and gives attention to the balance between botlt of them. Today, the medical profbssirttt is coloured with the s op h i s ti c at i o n o f’ the a c hi ev e m e nt s oJ- s c i e n c e an d t e c hn o I o gy- , *hereby ntore.focused on treatment and phltsical therap,v or physical. However, the internal value of the human being that capable of generating the therapy ruore eLfective treatment is less .fbcused. Taking meclicines ntay relieve pain or illness but not in the therapeutic treatment and healings ./br the patients. The value of the interttal.forces and strength owned by humon beings cctnnot be ignored at all becattse it is able to cure and to be therapist towards more effective self’-healing. In this paper, Ibn Qayltim al-Jawziyyahis methods o.f Ruqyah Therapy’ are chosen to put.forward.